STEAM TUBE DRYER PILOT PLANT TEST USING INDONESIAN LOW RANK COALS - Muhammad Hanif; Takayuki Noguchi (Badan Pengkajian dan Penerapan Teknologi, 2013)
Currently, Rembang Power is facing problems of insufficient power generation if fueled by low rank coals (LRC) with calorific value less than 4200 kcal/kg. Only good quality coals can generate maximum power, but good quality coals are getting more expensive and difficult to find. Therefore, pre-drying of LRC is required to improve Rembang power plant efficiency , and maximizes power generation. This work was aimed to investigate the performance of Steam Tube Dryer (STD) technology using LRCs from two different mining areas in East Kalimantan. A pilot plant of 100 kg/h of STD technology has been installed and operated in BPPT's Energy Center Laboratory in Puspiptek, Serpong. The drying test characteristic and reliability of STD were carried out in continuous operation within 120 hours. The moisture and particle size distribution of the dried coal products were also evaluated. Characteristics of the dried coal combustion test were conducted in one-D furnace and boiler simulator. The results showed that STD could achieve the appropriate drying speed with a significant reduction in total moisture of coals. It was also proved that STD was highly applicable to dry the Indonesian low rank coal with good combustion characteristics. Moreover, the test results will supply the engineering data for STD commercial application in the big-scale power generation.Keywords: Rembang power generation, steam tube dryer, low rank coal, combustion characteristic, coal moisture